Enigma of Retrotransposon Biology in Mammalian Early Embryos and Embryonic Stem Cells - Ying Yin; Liquan Zhou; Shuiqiao Yuan (Stem Cells International)
Retrotransposons comprise a significant fraction of mammalian genome with unclear functions. Increasing evidence shows that they are not just remnants of ancient retroviruses but play important roles in multiple biological processes. Retrotransposons are epigenetically silenced in most somatic tissues and become reactivated in early embryos. Notably, abundant retrotransposon expression in mouse embryonic stem cells (ESCs) marks transient totipotency status, while retrotransposon enrichment in human ESCs indicates naive-like status. Some retrotransposon elements retained the capacity to retrotranspose, such as LINE1, producing genetic diversity or disease. Some other retrotransposons reside in the vicinity of endogenous genes and are capable of regulating nearby genes and cell fate, possibly through providing alternative promoters, regulatory modules, or orchestrating high-order chromatin assembly. In addition, retrotransposons may mediate epigenetic memory, regulate gene expression posttranscriptionally, defend virus infection, and so on. In this review, we summarize expression patterns and regulatory functions of different retrotransposons in early embryos and ESCs, as well as document molecular mechanisms controlling retrotransposon expression and their potential functions. Further investigations on the regulatory network of retrotransposons in early embryogenesis and ESCs will provide valuable insights and a deeper understanding of retrotransposon biology. Additionally, endeavors made to unveil the roles of these mysterious elements may facilitate stem cell status conversion and manipulation of pluripotency.